Galleria mellonella as a Good Model to Study Acinetobacter baumannii Pathogenesis - Ye Tao (MDPI AG, 2021)
The invertebrate model, Galleria mellonella, has been widely used to study host–pathogen interactions due to its cheapness, ease of handling, and similar mammalian innate immune system. G. mellonella larvae have been proven to be useful and a reliable model for analyzing pathogenesis mechanisms of multidrug resistant Acinetobacter baumannii, an opportunistic pathogen difficult to kill. This review describes the detailed experimental design of G. mellonella/A. baumannii models, and provides a comprehensive comparison of various virulence factors and therapy strategies using the G. mellonella host. These investigations highlight the importance of this host–pathogen model for in vivo pathogen virulence studies. On the long term, further development of the G. mellonella/A. baumannii model will offer promising insights for clinical treatments of A. baumannii infection.